A sustentabilidade no processo de compras em instituições federais de ensino superior do estado de Goiás - Mendonça, Carmen Thereza Pietsch Cunha (2018)
This study refers to a research developed on the subject of Sustainable Public Procurement and its application in the Federal Institutions of Higher Education of the Midwest. Specifically, a diagnosis was made in these IFES and a Sustainable Purchasing Guide was developed. Regarding the methodology, this research was characterized by being qualitative, applied nature, exploratory, bibliographic, documentary, and based on multicaso study. The research's diagnosis was developed based on data obtained from the Purchasing Panel of the Federal Government and Management Reports on sustainable public procurement developed between the years 2012 to 2017 in the IFES of the Center West of Brazil. After that, it was proposed to use the sustainable public procurement guide, which includes environmental, social, economic and political criteria. Among the results obtained, the diagnosis showed that the degree of maturity in all the IFES is initial, since the sustainable purchases still cover few products, little budget, and thus the proposed Sustainable Procurement Guide proved to be appropriate for UFG. Sustainable public procurement should be used as a public policy instrument to promote sustainable development, as well as foster innovation and reduce costs.